Tasawuf dan Penyebaran Islam di Indonesia - Ghaffar, Nurkhalish A (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
Tasawuf or mysticism (famous name in western civilization) refers to one part of knowledge in Islam which was developed in 13th century. That is why tasawuf will become an interesting theme in a study. This essay in particular is an effort to explore the role of tasawuf in spreading Islam in Indonesia. As we know, there are a lot of theories which explain about the concept of islamization in Indonesia, i.e. theory of Gujarat, theory of Arab, theory of Parsi, the theory of China etc. Each of theory was named based on place of origin and time of arrival. According on that theory we will find that tasawuf was roled by Sufi which was gave more contribution to sustain the process of islamization in Indonesia. Afterwards, easily we can find a lot of evidence to prove that tasawuf played a role in spreading Islam in Indonesia, ie. There are a lot of thariqah which is leaded by a charismatic person like Hamzah Fansuri (w. 1590), Nuruddin ar-Raniri (w. 1658), Syekh Yusuf al-Makassar (1626-1699) etc. and also in each of annals had talked about islamization process in Indonesia ie. Hikayat raja-Raja Pasai which represented that tasawuf as popular views of Sultan.